A study of the clinical and radiological features in a cohort of 93 patients with a COL2A1 mutation causing spondyloepiphyseal dysplasia congenita or a related phenotype. (21st January 2015) - Terhal, Paulien A.; Nievelstein, Rutger Jan A. J.; Verver, Eva J. J.; Topsakal, Vedat; van Dommelen, Paula; Hoornaert, Kristien; Le Merrer, Martine; Zankl, Andreas; Simon, Marleen E. H.; Smithson, Sarah F.; Marcelis, Carlo; Kerr, Bronwyn; et al.
<x xml:space="preserve">Abstract</x> Type 2 collagen disorders encompass a diverse group of skeletal dysplasias that are commonly associated with orthopedic, ocular, and hearing problems. However, the frequency of many clinical features has never been determined. We retrospectively investigated the clinical, radiological, and genotypic data in a group of 93 patients with molecularly confirmed SEDC or a related disorder. The majority of the patients (80/93) had short stature, with radiological features of SEDC (n = 64), others having SEMD (n = 5), Kniest dysplasia (n = 7), spondyloperipheral dysplasia (n = 2), or Torrance‐like dysplasia (n = 2). The remaining 13 patients had normal stature with mild SED, Stickler‐like syndrome or multiple epiphyseal dysplasia. Over 50% of the patients had undergone orthopedic surgery, usually for scoliosis, femoral osteotomy or hip replacement. Odontoid hypoplasia was present in 56% (95% CI 38–74) and a correlation between odontoid hypoplasia and short stature was observed. Atlanto‐axial instability, was observed in 5 of the 18 patients (28%, 95% CI 10–54) in whom flexion‐extension films of the cervical spine were available; however, it was rarely accompanied by myelopathy. Myopia was found in 45% (95% CI 35–56), and retinal detachment had occurred in 12% (95% CI 6–21; median age 14 years; youngest age 3.5 years). Thirty‐two patients complained of hearing loss (37%, 95% CI 27–48) of whom 17 required hearing aids. The ophthalmological features and possibly also hearing loss are often relatively frequent and severe in patients with splicing mutations. Based on clinical findings, age at onset and genotype–phenotype correlations in this cohort, we propose guidelines for the management and follow‐up in this group of disorders. © 2015 Wiley Periodicals, Inc.